PENGARUH PENGUNGKAPAN KEANEKARAGAMAN HAYATI DALAM LAPORAN KEBERLANJUTAN TERHADAP NILAI PERUSAHAAN DENGAN TATA KELOLA PERUSAHAAN SEBAGAI VARIABEL MODERASI - Andika Prima Ertanta Tarigan; Warsito Kawedar (Diponegoro Journal of Accounting, 2020)
This study aims to examine the effect of biodiversity disclosure on firm value, with corporate governance as moderating variable. Independent variable used in this study is biodiversity disclosure which is proxied by biodiversity disclosure index (BDI). Dependent variable used in this study is firm value, which is proxied by Tobin’s Q. Meanwhile, the variable that moderates the relationship between disclosure of biodiversity to firm value is corporate governance, which is proxied by independent commissioners’ percentage and audit quality This study used purposive sampling method to select sample from the population. Based on this method, 66 samples of companies that listed on the Indonesia Stock Exchange and published their sustainability report on GRI website during 2014-2017 were obtained. Hypotheses testing is done by using multiple regression analysis. The results obtained in this study indicates that biodiversity disclosure has a significant positive effect on firm value. Meanwhile, corporate governance that moderates the relationship between biodiversity disclosure and firm value do not have a significant effect. Thus, it can be concluded that the influence between biodiversity disclosure in the sustainability report and firm value does not require moderation of corporate governance, that are proxied by using independent commissioners’ percentage and audit quality.